Solving Real-Life Problems: Future Mobile Technology Sophistication - Shafiq, Farhan; Ahsan, Kamran; Nadeem, Adnan (Mehran University Research Journal of Engineering and Technology; Vol 35 No 3 (2016): July Issue, 2016)
Almost all the human being real life concerned domains are taking advantage of latest technologies for enhancing their process, procedures and operations. This integration of technological innovations provides ease of access, flexibility, transparency, reliability and speed for the concerned process and procedures. Rapid growth of ICT (Information and Communication Technology) and MT (Mobile Technology) provides opportunity to redesign and reengineered the human routines’ life activities process and procedures. Technology integration and adoption in routine life activities may serves compensatory mechanism to assist the population in different manner such as monitoring older adults and children at homes, provides security assistance, monitoring and recording patients vital signs automatically, controlling and monitoring equipments and devices, providing assistance in shopping, banking and education as well. Disasters happened suddenly, destroy everything indiscriminately. Adoption and integration of latest technologies including ICT and MT can enhance the current disaster management process, procedures and operations. This research study focuses the impacts of latest and emerging technology trends in routine life activities and surrounds their potential strength to improve and enhance disaster management activities. MT is providing a promising platform for facilitating people to enhance their routine life activities. This research argue that integration and adoption of mobile computing in disaster management domain can enhance disaster management activities with promising minimizing error, quick information assembling, quick response based on technology manipulation and prioritizing action.